ACHIEVEMENT OF COMMUNITY HEALTH CENTER SEEN THROUGH ACCREDITATION RESULTS: CASE STUDY IN PUSKESMAS "X", IN SURABAYA - Meily Arovi Qulsum; Kurnia Sari; Adang Bachtiar; KM Taufiq (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Accreditation and recognition of a Community Health Center (Puskesmas) are given by an independent accredited organization, established by the Minister of Health after comply the accreditation standards. The accreditation achievement in East Java is at most of main level 76.7%. Puskesmas "X" is one of Puskesmas in Surabaya which has been accredited with basic level of status in 2015. This study aims to provide a comprehensive overview of the issues affecting the achievement of Puskesmas accreditation. Methods: This research is a qualitative descriptive study with in-depth interview and document searching using an accreditation instrument standard. Results: Based on accreditation results, the planning of the health centre was less appropriate because it was not based on identification of need and expectation. The mobilization and implementation was not working well due to lack of human health resource. Monitoring, control, and performance appraisal of the health centre have not been done. Conclusions: The accreditation of the health center, the Puskesmas X, in Surabaya is not only assessed by the document but also by the processes and system implementation activities. Achievement of Puskesmas accreditation status represents as a description of Puskesmas management and the result will have an impact on Puskesmas performance, and service quality.